PRACTICAL APPROACH IN TEACHING ENGLISH IN UZBEKISTAN - Radjabova Azima Temurovna (Scholar Express Journals, 2022)
This article analyzed hypothesis of the study is that if learners of any proposed EST course are involved in the selection of course material (reading and listening material) and in the design of the course, such involvement of the learners will enhance their interest and motivation level, foster their critical thinking skills, make them take part in various language activities enthusiastically and result in their effective learning. Moreover, such a step would make teaching-learning process enjoyable and pave the way for achieving the course objectives.
Keywords: Describing; Defining; Discussing; Analyzing